2019
DOI: 10.1002/cssc.201903139
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Temperature Charging and Aging Mechanisms of Si/C Composite Anodes in Li‐Ion Batteries: An Operando Neutron Scattering Study

Abstract: The addition of Si compounds to graphite anodes has become an attractive way of increasing the practical specific energies in Li‐ion cells. Previous studies involving Si/C anodes lacked direct insight into the processes occurring in full cells during low‐temperature operation. In this study, a powerful combination of operando neutron diffraction, electrochemical tests, and post‐mortem analysis is used for the investigation of Li‐ion cells. 18650‐type cylindrical cells in two different aging states are investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 51 publications
4
64
0
Order By: Relevance
“…Furthermore, it is shown that the relative lithiation/delithiation is influenced by the applied current and the competition between different transport processes. Richter et al [44] . recently studied low temperature charging and aging mechanisms of Si/Gr blended anodes using operando neutron scattering.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is shown that the relative lithiation/delithiation is influenced by the applied current and the competition between different transport processes. Richter et al [44] . recently studied low temperature charging and aging mechanisms of Si/Gr blended anodes using operando neutron scattering.…”
Section: Introductionmentioning
confidence: 99%
“…3f) and is consistent with the behavior of deposited Li during rest after charging. 5,[7][8][9][10][11][12]14,15,31 The main difference is that deposited Li metal often shows a dendritic micro structure, whereas the Li metal is compact in our experiment.…”
Section: Resultsmentioning
confidence: 66%
“…This is in accordance with results on re-intercalation of Li deposition by others. 12,[14][15][16][17] In cells with higher internal pressure, e.g. cylindrical cells, it is likely that Li depositions re-intercalate faster due to better contact with the electrode.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In literature, the mechanism of lithium metal deposition is mostly investigated for graphite anodes, [ 102,105,172–175,177,184,185 ] although it is also studied in Si/C composite anodes. [ 186 ] The phenomenon of lithium metal deposition on anodes is highly critical since it can reduce safety by dendrite growth [ 187 ] and exothermic reactions. [ 175,188 ] On graphite anodes, lithium metal deposition is favored during charging at low temperatures, [ 38,102,103,185 ] high charging C‐rates, [ 103,185 ] and high SOCs, [ 103 ] as well as their combination.…”
Section: Anodementioning
confidence: 99%